Revealing the Potential of Solamargine for Anti Metastasis and Angiogenesis Inhibition in Nasopharyngeal Carcinoma - Tang X; Ma C; Ren Y; Lv Y; He Y; Han L; Wu J (Journal of Inflammation Research)
Xiaojuan Tang,1,2 Changju Ma,2 Yuan Ren,1 Yuan Lv,1 Yongheng He,3 Ling Han,2 Jingjing Wu2 1Central Laboratory, Affiliated Hospital of Hunan Academy of Traditional Chinese Medicine, Changsha, 410006, People’s Republic of China; 2The Second Affiliated Hospital of Guangzhou University of Chinese Medicine, Guangzhou, 510120, People’s Republic of China; 3Department of Anorectal Surgery, Affiliated Hospital of Hunan Academy of Traditional Chinese Medicine, Changsha, 410006, People’s Republic of ChinaCorrespondence: Yongheng He, Department of Anorectal Surgery, Affiliated Hospital of Hunan Academy of Chinese Medicine, No. 58, Lushan Road, Yuelu District, Changsha, 410006, People’s Republic of China, Tel +86-13517401858, Email He13517401858@163.com Jingjing Wu, The Second Affiliated Hospital of Guangzhou University of Chinese Medicine, No. 111, Dade Road, Guangzhou, 510120, People’s Republic of China, Tel +86-15989137849, Email wujingjing6028@gzucm.edu.cnBackground: Nasopharyngeal carcinoma (NPC) is a major global health issue, especially in Southeast Asia. Solamargine (SM), an alkaloid from natural plants, inhibits various cancer cells. This study evaluates SM’s effects on invasion, migration, EMT markers, angiogenesis, and related pathways in the NPC-specific C666-1 cell line.Methods: In vitro assays, including wound healing, Transwell invasion, Western blot, and tube formation, were used to assess SM’s impact on C666-1 NPC and HUVEC cells. SM concentrations were 2 μM and 5 μM, with axitinib (4 μM) as the control. Network pharmacology and GO-KEGG enrichment analyses were conducted to explore SM’s targets and mechanisms in NPC.Results: SM significantly inhibited C666-1 NPC cell invasion and migration by reducing EMT markers Vimentin and Snail. In HUVEC cells, SM decreased viability, invasion, migration, and tube formation, likely through VEGF signaling inactivation, EZH2 inhibition, and miR-203a-3p upregulation. Network pharmacology and GO-KEGG analyses identified key targets and pathways, suggesting SM’s anti-NPC effects through multiple mechanisms.Discussion: SM inhibits NPC cell invasion and migration by regulating EMT, suppressing angiogenesis, and modulating key pathways. These findings highlight SM’s potential as an anti-cancer agent for NPC and provide new insights into its mechanisms. Network pharmacology and GO-KEGG analysis further identify its therapeutic targets, offering valuable directions for future drug development.Keywords: Nasopharyngeal carcinoma, solamargine, epithelial-mesenchymal transition, angiogenesis, network pharmacology